Identité Marseille - Pailhas, Roger; Marcos, Jean-Louis; Paire, Alain (Marseille : ARCA (Centre d'Art Contemporain), 1986)
Autard, Georges ; Baquié, Richard ; Bartolani, Judith ; Royer, Bernard ; Delbès, Jean-Louis ; Della-Noce, Gilbert ; Ducaté, Marie ; Fabre, Gérard ; Galland, Laurent ; Ibanez, Buy ; Klemensiewicz, Piotr ; Lagesse, Guy-André ; de La Souchère, Annie ; Lekhal, Noury ; Melgrani, Gilles ; Mezzapelle, François ; Michault, Patrick ; Milner, Judy ; Ruggirello, Jean-Claude ; Traquandi, Gérard
Identité Marseille, ARCA (Centre d'Art Contemporain), Marseille, 28 juillet - 30 septembre 1986
boek